Associations Between Global Competence and Right-Leaning Population: Evidence From PISA 2018 and European Social Survey - Vaitekaitis, Jogaila; Stumbrienė, Dovilė (Acta Paedagogica Vilnensia, 2022)
This study explores the relationship between 15-year-olds results in the PISA 2018 assessment of global competence and citizens’ political views. In particular, we look at the correlations of 18 EU nation-states citizens’ political preferences (right-leaning) and students’ non-cognitive skills, attitudes, and values. Data from the OECDs’ PISA global competence and European Social Survey for the year 2018 were used. After the analysis, it can be presumed that the higher share of the right-leaning population in the country is associated with lower students’ global competencies.
Keywords: European education; global competence; PISA; political right; far-right; linear regression analysis